Stress and food intake of nursing students of the University of the Philippines - Manila - Balcita, Kim O.; Bunquin, Marlene Daile T.; Calingo, Reneife Mae B.; Daguno, Nikolas Leandro R.; Eleno, Lea Sophia I.; Fernandez, Samantha Isabel Carmella T.; Galacan, Lourdes B.; Gomez, Julie Ann E.
The study aims to determine the relationship between the stress experience and food intake of the first year to fourth year students of the College of Nursing of the University of the Philippines — Manila officially enrolled in the second semester of AY. 2011 — 2012. The research design applied in the study is the cross-sectional design. Through a stratified random sampling, 30 participants were chosen from each year level. Instruments that were utilized include a short demographic questionnaire, the Student Nurse Stress Index form, and a 24-hour food recall form. The Food Exchange Lists for Meal Planning and Food and Nutrition Research Institute Food Pyramids were also utilized as guides in the analysis of the accomplished food recall forms. Through the Pearson product moment correlation analysis, it was found out that only meat and related products have a correlation with the stress experience. Analysis showed that this correlation is moderately negative. This means that there is a moderately inverse relationship between perceived stress experience and intake of meat and its related products. For all the other food products, however, the results are statistically insignificant implying that perceived stress experience has no correlation with the intake of the rest of the food categories.